Prognostic impact of admission time in infarct-related cardiogenic shock: an ECLS-SHOCK substudy - Schupp, Tobias; Thiele, Holger; Rassaf, Tienush; Abbas Mahabadi, Amir; Lehmann, Ralf; Eitel, Ingo; Skurk, Carsten; Clemmensen, Peter; Hennersdorf, Marcus; Voigt, Ingo; Linke, Axel; Tigges, Eike; et al. (JACC Cardiovascular interventions, 2024)
Background - The outcomes of patients with acute myocardial infarction complicated by cardiogenic shock (AMI-CS) and the efficacy and safety of extracorporeal life support (ECLS) may be affected by the timing of hospital admission. - Objectives - The present ECLS-SHOCK substudy sought to investigate the prognostic impact of on-hours vs off-hours admission and the efficacy of ELCS according to the timing of hospital admission time in AMI-CS. - Methods - Patients with AMI-CS enrolled in the multicenter, randomized ECLS-SHOCK trial from 2019 to 2022 were included. The prognosis of patients admitted during regular hours (ie, on-hours) was compared to patients admitted during off-hours. Thereafter, the prognostic impact of ECLS was investigated stratified by the timing of hospital admission. The primary endpoint was 30-day all-cause mortality. Statistical analyses included Kaplan-Meier, univariable, and multivariable logistic regression analyses. - Results - Of 417 patients enrolled in the ECLS-SHOCK trial, 48.4% (n = 202) were admitted during off-hours. Patients admitted during off-hours were younger (median age = 62 years [Q1-Q3: 55-69 years] vs 63 years [Q1-Q3: 58-71 years]; P = 0.036) and more commonly treated using initial femoral access for coronary angiography (79.0% [n = 158/200] vs 67.9% [n = 146/215]; P = 0.011). However, off-hours admission was not associated with an increased risk of 30-day all-cause mortality (off-hours vs on-hours: 46.0% [n = 93/202] vs 50.7% [n = 109/215]; OR: 0.83; 95% CI: 0.56-1.22). Furthermore, ECLS had no prognostic impact on 30-day all-cause mortality in patients with AMI-CS admitted during on-hours (50.5% [n = 52/103] vs 50.9% [n = 57/112]; P = 0.95; OR: 0.98; 95% CI: 0.58-1.68) or in patients admitted during off-hours (45.3% [n = 48/106] vs 46.9% [n = 45/96]; P = 0.82; OR: 0.94; 95% CI: 0.54-1.63). Finally, ECLS was associated with an increased risk of bleeding events, especially in patients admitted during on-hours. - Conclusions - The prognosis in AMI-CS was not affected by admission time with a similar effect of ECLS during on- and off-hours.
Online verfügbar: 14. Oktober 2024, Artikelversion: 14. Oktober 2024
Gesehen am 13.05.2025